Great migrations : official companion to the National Geographic channel global television event - Kostyal, K. M., 1951- (National Geographic, 2010)
In this magnificent companion to the groundbreaking 7-hour miniseries, animal journeys are illustrated with images by National Geographic-caliber photographers and with iconic stills from the film. Informational sidebars throughout the book highlight new technology, preeminent scientists and photographers in the field, and the backstories behind the memorable seven-part documentary.